2018
DOI: 10.1093/jn/nxy141
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns Affect the Gut Microbiome—The Link to Risk of Cardiometabolic Diseases

Abstract: Abstract Clusters of bacterial species within the gut microenvironment, or gut enterotype, have been correlated with cardiometabolic disease risk. The metabolic products and metabolites that bacteria produce, such as short-chain fatty acids, secondary bile acids, and trimethylamine, may also affect the microbial community and disease risk. Diet has a direct impact on the gut microenvironment by providing substrates to and promoting the colonization of resident ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 77 publications
1
49
0
1
Order By: Relevance
“…Previous human studies that investigated other a priori dietary patterns or indices (e.g. Healthy Eating Index, Mediterranean Diet Score and Healthy Food Diversity index) also showed that greater adherence to healthy diets was associated with increased abundance of other SCFA-producing microbes, such as Faecalibacterium prausnitzii (8,10) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous human studies that investigated other a priori dietary patterns or indices (e.g. Healthy Eating Index, Mediterranean Diet Score and Healthy Food Diversity index) also showed that greater adherence to healthy diets was associated with increased abundance of other SCFA-producing microbes, such as Faecalibacterium prausnitzii (8,10) .…”
Section: Discussionmentioning
confidence: 97%
“…Not unlike the complex and interactive nature of the microbiome, dietary habits are multidimensional with many interrelated components. Recently, Bowyer et al and Maskarinec et al demonstrated the utility of a priori dietary patterns or indices for capturing and controlling for variation in the gut microbiome due to the effects of participants' diets (8)(9)(10)(11)(12) . The Dietary Inflammatory Index (DII ® ) assesses the balance of pro-and anti-inflammatory dietary factors based on literature-derived associations between various dietary components and inflammatory biomarkers.…”
mentioning
confidence: 99%
“…This is a natural approach, given that in a diet, nutrients and foods eaten together do not act in isolation, but rather show synergistic effects [39]. Thus, dietary patterns and overall diet analysis are more robust way of understanding diet-disease relationship [40,41]. For instance, assessment of dietary patterns is suggested as an important indicator of chronic low-level systemic inflammation, which is an associated factor of chronic diseases [42].…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota influences fatty acid oxidation, lipogenesis, satiety, and metabolic endotoxemia. Effects of gut bacteria on risk for CVD, and T2D is inconsistent, and these effects are mediated via metabolites such as short‐chain fatty acids (SCFAs), secondary bile acids, LPS, and trimethylamine (TMA) . Of these, TMA produced by gut bacteria through choline, phosphatidylcholine, and l ‐carnitine can be oxidized to TMA N‐oxide (TMAO).…”
Section: Impact Of Gut Microbiota On Obesity and Inflammationmentioning
confidence: 99%
“…Of these, TMA produced by gut bacteria through choline, phosphatidylcholine, and l ‐carnitine can be oxidized to TMA N‐oxide (TMAO). This TMAO is associated with increased CVD risk in humans . Moreover, a negative association between bacteria diversity and overweight/obesity has been studied, although some studies have shown that bacterial diversity increases in obese versus non‐obese subjects .…”
Section: Impact Of Gut Microbiota On Obesity and Inflammationmentioning
confidence: 99%